ALTRUISME GURU DALAM PERSPEKTIF ISLAM - Farhad Muhammad; Abdul Muhid (IAIN Ponorogo, 2022)
AbstractTeacher Altruism in an Islamic Perspective. Altruism as an active attitude of a person to help others has a significant social impact, in Islam altruism is better known in its terms which is one of the basic attitudes of a Muslim, especially for teachers who are central figures in the education of future generations to become the better person should be one with altruism. This study aims to reveal the similarities and differences between altruism and itsar, and altruistic attitudes of teachers. The method in this study is a literature review, the source of the data is taken from literature and journals related to the research topic. The results of this study are altruism and itsar have similarities in the meaning of both which refer to individual actions that want good for others without getting reciprocity, along with indicators in the form of; attitude of giving, cooperation, donation, helping, honest, and generous, while the difference lies in the spiritual aspect in Itsar’s indicators, so that makes itsar more perfect than altruism. Mu'tsir teachers in Islam are teachers who prioritize the interests of students compared to the teacher himself, making indicators of altruism as the basis of their competence, by adding spiritual competence contained in itsar as a manifestation of faith and charity as a Muslim, and as an accountability answer before Allah SWT. AbstrakAltruisme Guru Dalam Perspektif Islam.Altruisme sebagai sikap aktif seseorang untuk membantu orang lain memiliki dampak sosial yang signifikan, dalam islam altruismelebih dikenal dalam term itsar yang merupakan salah satu sikap dasar seorang muslim, terlebih bagi Guru yang merupakan tokoh sentral dalam pendidikan generasi mendatang untuk menjadi pribadi yang lebih baik haruslah merupakan seorang dengan sikap altruisme. Penelitian ini bertujuan mengungkapkan persamaan dan perbedaan antara altruisme dan itsar, dan sikap-sikap altruisme guru. Metode dalam penelitian ini merupakan kajian pustaka, sumber datanya diambil dari literatur dan jurnal yang terkait dengan topik penelitian. Hasil penelitian ini adalah altruisme dan itsar memiliki persamaan dalam pengertian keduanya yang merujuk pada tindakan individu yang menghendaki kebaikan bagi orang lain tanpa mendapatkan timbal balik, berikut indikatornya yang berupa; sikap memberi, kerjasama, donasi, menolong, jujur, dan dermawan, sedangkan perbedaannya terletak pada keberadaan aspek spiritual dalam indikator yang dimiliki term Itsar, sehingga cakupan itsar bisa menjadi lebih sempurna dari altruisme. Guru yang mu’tsir dalam Islam merupakan guru yang lebih mengutamakan kepentingan peserta didik dibandingkan dengan diri guru itu sendiri, menjadikan indikator altruisme sebagai dasar kompetensi yang dimilikinya, dengan menambahkan kompetensi spiritual yang terdapat pada itsar sebagai perwujudan iman dan amalnya sebagai muslim, dan sebagai pertanggung jawabannya dihadapan Allah SWT.